Evidencing the diversity and needs of adjustment of the nutritional requirements for hydrocarbon-degrading activity of Pseudomonas aeruginosa adapted to harsh conditions using 2n full factorial design. Issue 73 (26th September 2017) - Attar, Al Zahraa; Jaoua, Samir; Ahmed, Talaat A.; Al Disi, Zulfa; Zouari, Nabil
Abstract : Nutritional requirements of the most widely used bacterium, P. aeruginosa, was shown to be necessary to predict in advance to prevent failure of oil hydrocarbon bioremediation due to weathering processes. Abstract : To overcome the partial or complete failure of oil hydrocarbon bioremediation due to weathering processes, occurring in most oil producing and spilling areas, nutritional requirements of the most widely used bacterium, Pseudomonas aeruginosa, were shown to be necessary to predict in advance, because they affect its activity to remove categories of polluting hydrocarbons. This study showed a high diversity of the relationship between the metabolism and the biological activity of Pseudomonas aeruginosa . The Gulf area represents a good site to isolate three highly adapted Pseudomonas aeruginosa strains from different highly polluted and weathered soils. The close relationship between the bacterial strains and the micro environment composition was investigated. Statistical analysis, using 2 3 factorial design, of the correlation between nutritional requirements of three Pseudomonas aeruginosa strains and their potential to degrade diesel hydrocarbons was carried-out. Long term adaptation of hydrocarbon-degrading bacteria to weathered hydrocarbons and harsh conditions provides them with specific metabolic potentialities that vary from one isolate to another although belonging to the same species. The sensitivity of hydrocarbon-degrading bacterial growth and the biological activity of the three isolates were analyzed. The optimal media composition in term of carbon, nitrogen and phosphorous concentrations related to their C/N/P ratios varied among the isolates with a maximal biomass production reaching 90 × 10 7 CFU ml −1 . The significance of the first and second order interactions of C, N and P sources showed high variability in the impact on growth and biological activity. Hydrocarbon removal was much higher for high molecular weight ones, reaching almost 90% for strains under specific growth conditions for each isolate. This is of high importance for remediating weathered oil. Mostly, all strains expressed enhanced removal activity by the second week of incubation. However, removal and conversion of diesel hydrocarbons was found to be highly sensitive to the availability and balance of the nutrients and varied from one Pseudomonas aeruginosa strain to another. This is of great importance from the practical point of view for spilled oil bioremediation using Pseudomonas aeruginosa .